2022
DOI: 10.1177/11786361221113916
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Quality and Public Health Risk of Ready-to-Eat Foods in Developing Countries: Systematic Review and Meta Analysis

Abstract: Background: Ready-to-eat foods are foods that are consumed at the point of sale or later, without any further processing or treatment. Foodborne diseases are on the rise worldwide, involving a wide range of diseases caused by pathogenic bacteria, and are becoming a public health problem. Therefore, this study sought to identify and determine the bacteriological quality and public health risks in ready-to-eat foods in developing countries. Methods: The studies published from 2012 to 2020 were identified through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…The isolated bacteria from the food samples comprise mainly members from the family Enterobacteriacea known to be associated with food borne illness. This agrees with the findings of Mengistu et al (2022) The results of antibiotic susceptibility test on isolated bacteria from location X, Y and Z. According to standards by CSLI (2015) based on the zones of inhibition, all the bacteria isolates showed resistance to the various antibiotics analyzed.…”
Section: Discussionsupporting
confidence: 90%
“…The isolated bacteria from the food samples comprise mainly members from the family Enterobacteriacea known to be associated with food borne illness. This agrees with the findings of Mengistu et al (2022) The results of antibiotic susceptibility test on isolated bacteria from location X, Y and Z. According to standards by CSLI (2015) based on the zones of inhibition, all the bacteria isolates showed resistance to the various antibiotics analyzed.…”
Section: Discussionsupporting
confidence: 90%
“…Calonico, Delfino, Pesavento, Mundo, and Lo Nostro (2019) reported that washing salads before consumption was effective in reducing the microbiological load, especially E. coli . In various studies, K. pneumoniae , which causes food‐borne outbreaks, have been reported in retail foods in different countries (Afolabi et al, 2012; Makinde et al, 2020; Mengistu, Belami, Tefera, & Asefa, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This outbreak largely affected patients who had adopted a vegan or vegetarian diet. An estimated 5% of Canadians adhere to a plant-based diet (( 8 )). In addition, age and gender differences are apparent among persons adhering to plant-based diets such as vegetarianism, which is practiced more commonly among females and younger adults (( 9 )), consistent with the patient demographics in this outbreak.…”
Section: Discussionmentioning
confidence: 99%